Normative construction of the life care contract in the Draft Code on Obligations and Contracts and in the Predraft of the Civil Code of the Republic of Serbia - Đurđević Dejan B. (Anali Pravnog Fakulteta u Beogradu)
The article provides a comparative analysis of the legislative proposals contained in the Draft Code on Obligations and Contracts and the Predraft of the Civil Code of the Republic of Serbia. The text explains the historical development of the life care contract in Serbian legislation and the circumstances that formed it and placed it into codification devoted to law on inheritance. The author is strongly critical of the proposals in the Predraft because its authors did not take advantage of the opportunity to create new rules that would be adequate in contemporary circumstances, but rather copied the existing rules of the Law on Inheritance, which have long been recognized as deficient in certain aspects. The author concludes that the life care contract deserves a new and more comprehensive legislative regime, which would respond to practical needs and solve existing dilemmas.